Total Cholesterol and Blood Sugar Levels in Type 2 Diabetes Mellitus Patients - Citra TRISNA; Anis SUFIYANTI; Mardyana NIZAR; Hadits Lissentiyana ARMAL; Slamet; Slamet WARDOYO; Jessica Juan PRAMUDITA (Modern Medicine)
Diabetes Mellitus is a syndrome characterized by high blood sugar levels and various metabolic disorders caused by hormonal imbalance. The aim of this study was to determine the relationship between total cholesterol levels in type 2 diabetes mellitus sufferers at Krakatau Medika Hospital, Cilegon City. This research uses a cross-sectional research design. The samples in this study amounted to 30 samples. The results of the study showed that total cholesterol levels in type 2 DM sufferers were 68.7%, totalling 22 patients. Frequency distribution of total cholesterol levels based on age with a percentage of 76.5%, totalling 13 patients aged > 50 years. Based on gender, with a percentage of 89.5%, 17 patients were female. Based on body mass index with a rate of 64%, there were 16 patients with a BMI ≥ 27 (obese). Based on statistical tests show that there is a relationship between total cholesterol levels in type 2 DM sufferers with a p-value of 0.001 (p < 0.05).